Results 1 to 2 of 2

Math Help - Given f(x) = (x - 1)/4 and g(x) = 4x - 3, find f(g(a)) and g(f(-b)).

  1. #1
    Newbie
    Joined
    May 2009
    Posts
    7

    Given f(x) = (x - 1)/4 and g(x) = 4x - 3, find f(g(a)) and g(f(-b)).

    Given f(x) = (x - 1)/4 and g(x) = 4x - 3, find f(g(a)) and g(f(-b)). A.) f(g(a)) = a +1, g(f(-b)) = b - 4 B.) f(g(a)) = a, g(f(-b)) = -b C.) f(g(a)) = 4a -1, g(f(-b)) = b +1 D.) f(g(a)) = a -1, g(f(-b)) = -b - 4
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    skeeter's Avatar
    Joined
    Jun 2008
    From
    North Texas
    Posts
    12,134
    Thanks
    1013
    Quote Originally Posted by Foxy_Girl18 View Post
    Given f(x) = (x - 1)/4 and g(x) = 4x - 3, find f(g(a)) and g(f(-b)). A.) f(g(a)) = a +1, g(f(-b)) = b - 4 B.) f(g(a)) = a, g(f(-b)) = -b C.) f(g(a)) = 4a -1, g(f(-b)) = b +1 D.) f(g(a)) = a -1, g(f(-b)) = -b - 4
    what do you know about function composition?
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Replies: 8
    Last Post: March 22nd 2011, 05:57 PM
  2. Replies: 2
    Last Post: July 5th 2010, 09:48 PM
  3. Replies: 1
    Last Post: February 17th 2010, 04:58 PM
  4. Replies: 0
    Last Post: June 16th 2009, 01:43 PM
  5. Replies: 2
    Last Post: April 6th 2009, 09:57 PM

Search Tags


/mathhelpforum @mathhelpforum